2019
DOI: 10.1111/ajd.13206
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in the treatment of paediatric alopecia areata: Retrospective case series and updated meta‐analysis

Abstract: Background/Objectives: There is a paucity of data regarding the efficacy and safety of methotrexate (MTX) in childhood alopecia areata (AA), particularly in an Australasian cohort. We aimed to assess the efficacy and safety of MTX in childhood AA based on our institutional experience.Methods: A retrospective chart review was performed from patients treated by a consultant dermatologist. Consecutive children with AA treated with MTX seen between 2010 and 2019 were analysed. A meta-analysis of proportions was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
1
18
1
3
Order By: Relevance
“…Furthermore, the fact that most comorbidities appear to be already present at AA onset may have important clinical implications, as this may affect which therapy will be most appropriate for the individual patient. Indeed, for some patients, one drug may be contraindicated either because of co‐medication or because of the risk of exacerbation of existing conditions (as seen, for example with some psoriasis treatments and neurological disorders), 15 whereas other drugs may treat not only AA but also have beneficial effects on selected comorbidities 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that most comorbidities appear to be already present at AA onset may have important clinical implications, as this may affect which therapy will be most appropriate for the individual patient. Indeed, for some patients, one drug may be contraindicated either because of co‐medication or because of the risk of exacerbation of existing conditions (as seen, for example with some psoriasis treatments and neurological disorders), 15 whereas other drugs may treat not only AA but also have beneficial effects on selected comorbidities 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…A recent case series on pediatric patients demonstrated a 70% success rate of methotrexate for AA with no serious side effects, other than nausea and vomiting [15]. Another study conducted on children with AA reported regrowth with methotrexate in over half of the patients studied, demonstrating that methotrexate is an effective medication in pediatric AA.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, an updated meta-analysis for pediatric patients with AA on methotrexate showed success rates of 49.7%, recurrence rates of 30% and side effects in only 15.7% of cases. However the largest sample size encountered included 14 children [15]. Therefore, more information about this therapy should be investigated in order to make reasonable conclusions about using methotrexate in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50] The adverse effects of systemic methotrexate in children with alopecia areata included nausea, vomiting, abdominal discomfort, abnormal liver function test results, neutropenia, migraine, leg weakness and tooth sensitivity. [48][49][50][51][52][53] Topical minoxidil [the highest level of evidence: III; the total number of patients: 9; response rate in monotherapy: 44% (4/9); global response rate: 44% (4/9); relapse rate: 0% (0/ 1)]…”
Section: Resultsmentioning
confidence: 99%
“…However, it was also reported to be effective in monotherapy with the response rate of 100% (10/10) 48‐50 . The adverse effects of systemic methotrexate in children with alopecia areata included nausea, vomiting, abdominal discomfort, abnormal liver function test results, neutropenia, migraine, leg weakness and tooth sensitivity 48‐53 …”
Section: Resultsmentioning
confidence: 99%